Vulnerabilidade social e desigualdade diante da morte por Covid-19 em Fortaleza (2020-2021) - Oliveira, Rebeca de Souza (2023)
The covid-19 pandemic has ravaged the world since the first half of 2020, causing serious consequences in the field of collective health. In Fortaleza, capital of the State of Ceará, the exponential increase in confirmed cases and, as a result, the high mortality rates from covid-19, especially in areas that are home to more socially vulnerable residents, were the ones that suffered most from the collapse of the system. of health. The urban landscape and spatial organization reveal the social and economic inequalities in Fortaleza, with neighborhoods concentrating a more vulnerable population. In these areas of the city, there was a high number of death records, which may be influenced by social and economic factors, such as age, comorbidities, gender, level of education, type of occupation, cultural aspects, small housing and the partial or non-existent social isolation, which was an important preventive measure to minimize the transmissibility of the disease. This dissertation aims to analyze the impacts caused by the covid-19 pandemic, mainly in the most vulnerable population, correlating with social and economic aspects and other indicators of social vulnerability. The analyzes contained in the work simulate descriptive studies, in order to have a better understanding of the epidemiological scenario of the disease and its space-time dynamics, carried out from the survey of secondary data. Thus, the spatial analyzes carried out in the course of this research were based on the location data of patients affected by the disease, obtained from the address (streets) of residence, comprising a high level of information detail, enabling the georeferencing of these addresses and representing them on thematic and cartographic maps of the spatial distribution of covid-19. In this scenario, analyzes carried out based on geographic science and geoprocessing techniques have become increasingly relevant in understanding the health-disease process involving space. In the municipality of Fortaleza, transmission began in neighborhoods with a very high HDI, where the highest number of confirmed cases were concentrated. However, the distribution of covid-19 is not homogeneous, especially of deaths, as the highest records occur in neighborhoods with the most vulnerable population, especially in the first epidemic wave, in 2020. Considering these factors, we will also analyze the distribution of cases and the deaths that occurred in Region 2, which stands out due to the presence of socio-spatial segregation and juxtaposition, as there is great social and economic diversity in this region, with the presence of neighborhoods with a very high HDI, coexisting with subnormal agglomerations, slums, hand barns of domestic services and others, such as the Vicente Pinzon neighborhood, which has a population of high social vulnerability and high mortality rates due to covid-19.